Investigation of The Ambient Nitrogen Oxides (NOx) Trends at Tronoh, Perak - Farelle, Charles Joseph (Universiti Teknologi PETRONAS, 2017)
In these days, the emissions of nitrogen oxides and nitrogen dioxide into ambient air has become one of the most concerned issue. As we all aware, the major contributor to these pollutants are industrial activities and vehicles. The area whereby industrial development and increase in number of vehicles is significant, will result in more total nitrogen oxides and nitrogen dioxide emitted to the air. This situation will cause tremendous effect to human, plants, and animals. In fact, these pollutants will become more complex when it reacts with other compounds to form secondary air pollutant. Hence, this study aims to determine the effect of industrial activities and vehicles to the concentration level of nitrogen oxides and nitrogen dioxide in selected area as well as the influence of temperature and relative humidity to the trend of pollutant’s concentration.